Monte Carlo simulation and parameterized treatment on the effect of nuclear elastic scattering in high-energy proton radiography - 许海波 郑娜 (Chinese physics C, 2015)
A version of Geant4 has been developed to treat high-energy proton radiography. This article presents the results of calculations simulating the effects of nuclear elastic scattering for various test step wedges. Comparisons with experimental data are also presented. The traditional expressions of the transmission should be correct if the angle distribution of the scattering is Gaussian multiple Coulomb scattering. The mean free path（which depends on the collimator angle） and the radiation length are treated as empirical parameters, according to transmission as a function of thickness obtained by simulations. The results can be used in density reconstruction, which depends on the transmission expressions.